„i / ta wielka łapka / na ludzi” – o podmiocie w poezji Ewy Lipskiej - Marciniak, Paweł (Przestrzenie Teorii, 2021)
The article concerns the idea of the subject’s evolution in the poetry of Ewa Lipska. The article presents the unexplored path of subjectivity’s development in selected poems by this Cracovian poet. The main research concept regards the interpretation of particular poems from the perspective of current philosophical problems, connected with posthumanism, which is understood here as the ability to go beyond the bounds of humanism, a revision of previous humanistic assumptions. The essential change of direction in the reception of Ewa Lipska’s writings could be perceived as a result of the interpretation contained in this article.